Fabrication of Sustainable Sand Brick with An Additive of Elastomer Type Waste Material - ABDUL RAHMAN, MOHD SYAHRIL ASHRAF (Research Progress in Mechanical and Manufacturing Engineering, 2022)
At present, the demand for adding recycled materials such as rubber to construction products is becoming more and more important in the production of bricks. Using waste tyres in brick or concrete mixes can reduce the consumption of raw materials. Waste tyres can be used as fine aggregate, coarse aggregate, or part of both. It can be used as an additive to produce sand bricks. Therefore, a mixture of waste tyres is used as part of the sand substitute in sand bricks, with emphasis on thermoplastic elastomers. This study aims to develop sustainable bricks using waste tyres and compare the density, compressive strength, and water absorption efficiency of sustainable bricks and conventional bricks. As part of the sand replacement, 15 specimens were prepared and mixed with different percentages of rubber crumb content, 5%, 10%, and 15%, respectively. The bricks are formed with mould size of 215mm in length, 100mm in width, and 60mm in depth. Density, compressive strength, and water absorption tests carried out and the bricks were tested on the 7th and 28th days. The results obtained show that the compressive strength recorded with 5% rubber crumbs of fine aggregate is not much different from that of traditional sand bricks. This indicates that as the number of rubber crumbs uses as a substitute for fine aggregate in bricks increases, the strength and workability density of concrete will decrease. On the other hand, the water absorption test shows that the rubber-containing bricks have better water absorption capacity. In this study, it was found that 5% rubber is the best percentage to partially replace fine aggregates in bricks production. However, the test results of all percentages are not significantly different from those of conventional bricks. To maintain the mechanical properties of concrete, the rubber powder used to replace aggregate shall not exceed 15%.